Optimizing Defense Acquisition for Weapon System Integration in an Integrated Defense Posture Based on SWOT and AHP - Hidayatullah, Syarif; Saleh, Basuki Rahmad; Santoso, Budi; Rudy , Elphis; Rahayu, Dian Diana; Saputro, Wisnu; Yunianto, Yunianto; Yusgiantoro, Purnomo; Midhio, I Wayan (PT FORMOSA CENDEKIA GLOBAL, 2025)
Weapons system acquisition is a strategic element in building a resilient and integrated national defense posture. This process faces significant challenges, such as limited coordination between the Ministry of Defense, the TNI Headquarters, and the Armed Forces Headquarters, budget constraints, and geopolitical influences that often hinder its effectiveness. This study explores a strategic approach based on inter-service coordination, technological innovation, and sustainability to create an adaptive and responsive defense posture to threats. Using a qualitative approach, the study analyzes data from academic literature and case studies of defense acquisition practices. This study integrates a SWOT analysis to identify the strengths, weaknesses, opportunities, and threats of each option in the Analytic Hierarchy Process (AHP). AHP, although widely used, faces criticism regarding the subjectivity in setting criteria and sub-criteria. A SWOT analysis helps balance these potential subjective biases through a comprehensive data-based evaluation, thereby optimizing the decision-making process. The findings show that the integration of advanced surveillance technologies, such as long-range radars, multi-role drones, and satellite systems, significantly enhances operational effectiveness.